Ácido giberélico e períodos de vernalização no crescimento, florescimento, produtividade e citogenotoxicidade do óleo essencial de Lavandula spp. - Puhl, Andressa Janaína (2023)
Lavanda (Lavandula spp.) are exotic plants that have several therapeutic properties, as well as produce an essential oil that is widely used in the pharmaceutical, cosmetic and food industries. The use of management techniques that enable and increase cultivation in quantity and quality of production, especially for those who may present difficulties in developing in adverse conditions to those of origin, can serve as an alternative for the innovation and production of new species. The lavanda shows popularity and growing interest in Brazil, however, little is known about their behavior through management with plant hormones and vernalization. The work aimed to determine the influence of the application of gibberellic acid (GA3) and vernalization periods in the growth, flowering, and productivity of essential oil and on the cell division and genetic material of Allium cepa L. The experiments were conducted in the Department of Phytotechnia of the UFSM. The first experiment was conducted in the field to test the application of four concentrations of GA3 (100, 200, 400 and 600 mg L-1 , plus 0 mg L1 , as water control, in two species of Lavandula spp. (Lavandula stoechas L. and Lavandula angustifolia Mill.). The second experiment was carried out in a cold chamber, followed by cultivation in the house of vegetation, with the same species, vernalized for 0, 2, 4, 6, 8, 10 and 12 weeks at 4ºC ± 1ºC. The variables analyzed were: height, diameter, and number of branches per plant, days for the beginning of flowering (DPF), percentage of plants and branches with inflorescences (PPI and PRI,%), number of inflorescences up to 3 cm and greater than 3 cm, fresh and dry mass of inflorescences and leaves, A third experiment was conducted in the Plant Cytogenetics Laboratory of the Department of Biology of the UFSM, to evaluate the genotoxic and antiproliferative effect of the essential oil of both experiments in the concentration of 0.05%, through the test of Allium cepa. The results showed that L. stoechas presented satisfactory and superior responses to L. angustifolia cultivation in the Central Region of Rio Grande do Sul, with exogenous application of GA3 400 and 600 mg L-1 and vernalization for up to 4 weeks in a cold chamber at 4ºC±1°C, increasing on growth, the number of inflorescences, content, and yield of the essential oil of inflorescences and leaves. Concentrations of 400 and 600 mg L-1 , anticipated the flowering as well as, higher production of inflorescences for L. angustifolia, however, the flowering occurred only after application in summer and was unsatisfactory for the extraction of the essential oil from the inflorescences. The vernalization of 10 to 12 weeks at 4ºC ± 1ºC, was necessary to induce the flowering of L. angustifolia, and anticipate the blooming and increase in height, but the subsequent exposure to high air temperatures, negatively influenced the number of inflorescences, content and yield of the essential oil of leaves. The essential oils at 0.05% have proliferation potential of cell division and genotoxic activity, due to the observation of chromosomal irregularities.